WEATHER CONDITIONS AND ITS RELATION WITH DENGUE INFECTION IN CENTRAL JAKARTA 2018-2020 - Hasibuan, Amirah Tsabitah Zain (HIGEIA (Journal of Public Health Research and Development), 2023)
ABSTRACT In 2019, Dengue incidence rate in DKI Jakarta was reported at 82.45 per 100,000 population. An increase in Dengue infection occurred, one of which is in Central Jakarta. One of the environmental factors that play major role in Dengue transmission is climate because Dengue virus and mosquitoes are sensitive to environment. This study aims to present the relationship between Dengue and weather conditions in Central Jakarta in 2018–2020. This research is observational analytic research. Data sources came from Central Jakarta City Health Sub-agency and Meteorology, Climatology and Geophysics Agency. Data analysis was performed univariately and bivariately using Rank Spearman test. The results of the analysis showed no relationship between rainfall (p = 0.072, r = 0.304), temperature (p = 0.164, r = -0.237), and wind speed (p = 0.704, r = -0.066) and dengue. However, there’s relationship between humidity and Dengue (p = 0.000, r = 0.592). The conclusion of this study is weather conditions (rainfall, temperature, and wind speed) in Central Jakarta don’t have significant relationship with Dengue. ABSTRAK Pada tahun 2019, incidence rate Dengue di DKI Jakarta dilaporkan sebesar 82,45 per 100.000 penduduk. Peningkatan infeksi Dengue terjadi salah satunya di Jakarta Pusat. Salah satu factor lingkungan yang berperan besar dalam penyebaran Dengue adalah iklim karena virus Dengue dan nyamuk sensitif terhadap lingkungan. Penelitian ini bertujuan untuk mempresentasikan hubungan infeksi Dengue dan kondisi cuaca di Jakarta Pusat tahun 2018–2020. Penelitian merupakan penelitian analitik observasional. Sumber data berasal dari Suku Dinas Kesehatan Kota Jakarta Pusat dan Badan Meteorologi, Klimatologi, dan Geofisika (BMKG). Analisis data dilakukan secara univariat dan bivariat menggunakan uji Rank Spearman. Hasil analisis menunjukkan tidak adanya hubungan antara curah hujan (p = 0.072, r = 0.304), suhu (p = 0.164, r = -0.237), dan kecepatan angin (p = 0.704, r = -0.066) dengan infeksi Dengue. Walaupun begitu, terdapat hubungan yang signifikan antara kelembaban dan infeksi Dengue (p = 0.000, r = 0.592). Kesimpulan dari penelitian ini adalah kondisi cuaca (curah hujan, suhu, dan kecepatan angin) di Jakarta Pusat tidak memiliki hubungan yang bermakna terhadap kejadian infeksi Dengue.